The mcpC mutant of Salmonella enteritidis exhibits attenuation and confers both immunogenicity and protective efficacy in mice - Zhang, Lu; Chen, Li; Zhang, Xuqiang; Li, Yang; Zheng, Qingfeng; Li, Yun; Li, Ning; Shi, Qiumei; Zhang, Yanying; Wu, Tonglei (Frontiers in Microbiology, 2025)
BackgroundSalmonella enteritidis (SE) is a Gram-negative, facultative anaerobic intracellular pathogen that not only causes disease and mortality in livestock and poultry but also contaminates animal-derived products, leading to foodborne illnesses in humans. This presents a significant threat to public health. To eliminate this pathogen, the development of novel vaccines targeting SE is imperative. Attenuated live vaccines are capable of eliciting robust immune protection against SE.MethodsIn this study, an mcpC gene deletion strain (ΔmcpC) was constructed by the wild strain C50336, to evaluate its potential as a genetically engineered attenuated live vaccine. The virulence of ΔmcpC was assessed by examining its resistance to environmental stresses, biofilm formation capacity, motility, adhesion, invasion ability, intracellular survival, LD50, expression levels of virulence genes, and in vivo colonization ability. Furthermore, the immunogenicity of ΔmcpC was analyzed in mice by measuring specific IgG and SIgA antibody levels, lymphocyte proliferation, cytokine expression, and the protective efficacy of ΔmcpC vaccination.ResultsCompared to the wild-type strain, ΔmcpC exhibited no significant changes in biofilm formation or adhesion to Caco-2 cells. However, ΔmcpC showed significantly reduced survival under acidic, alkaline, thermal, and oxidative stress conditions; markedly diminished motility; weakened invasion of Caco-2 cells; and reduced intracellular survival in RAW264.7 macrophages. The LD50 of ΔmcpC increased by 30-fold, and the expression levels of certain virulence genes were significantly downregulated. Additionally, ΔmcpC demonstrated significantly decreased colonization in the liver, spleen, and cecum of mice, indicating attenuated virulence. Immunization with ΔmcpC induced the production of specific IgG and SIgA antibodies, enhanced lymphocyte proliferation, upregulated cytokine expression, and achieved a 100% survival rate in immunized mice. These findings indicate that ΔmcpC provides effective immune protection in mice.ConclusionThis study demonstrates that deletion of the mcpC gene attenuates the virulence of SE. The ΔmcpC offers strong immune protection in mice, providing a solid foundation for the development of genetically engineered attenuated live vaccines against SE.